Transformasi Financial Behavior Mahasiswa Medan:Peran Financial Literacy, Financial Attitude dan Financial Socialization Agents - Ginting, Sugianta Ovinus; Perangin-angin, Naca; Br. Ginting , Litka Tiadoraria; Ginting, Mbayak (Owner : Riset dan Jurnal Akuntansi, 2024)
Complex economic problems lead individuals to continue trying to find solutions to meet their needs. Individual needs and desires that are unlimited and supported by a never-satisfied nature will encourage individuals to behave consumptive. This will have a negative impact and cause personal financial problems if you are unable to implement good financial behavior. Nowadays, students become agents of change who actively use information technology which results in students being trapped in a pattern of consumerism. Every individual must have financial behavior. It is good to be able to balance income and expenses so that you can meet your living needs and not get trapped in financial difficulties. This research was conducted to find out if financial literacy, financial attitude and financial socializations agents have an influence on financial behavior of Medan City students. The object of this research is students in the city of Medan with a population whose number is unknown and can be categorized as infinite. Therefore, the population size is infinite and can only be explained qualitatively. The sampling technique used is non probability sampling. Nonprobability sampling is a sampling technique that does not provide equal opportunities for each element or member of the population to be selected as a sample. In this research using quota sampling. The data analysis technique used in this research is multiple linear regression technique. The results of this research are partial tests of variables financial attitude dan financial socialization agents positive and significant effect on financial behavior, while variable financial literacy has no effect on financial behavior.